(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article considers that any organization’s website must be your own memorable face, while visitors should instinctively understand that the organization close to him. That is, in the minds of the visitor should have a vpechetlenie that the organization produces a product that is useful for him personally. Internet resource should have a catchy ‘title». Its main task – to attract the attention of visitors to the main message of the organization. One of the important methods of development and promotion of pages on the Internet is that the site can provide not only information concerning solely the organization, but also to be more versatile resource. Modern information society dictates the conditions under which all less time searching for the right information, at the same time, in some cases the person himself does not know exactly what interests him.